Karakteristik Wisatawan Nusantara yang Berkunjung ke Kota Solo - rizky nugroho (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2019)
Solo City located in Central Java Province with potential cultural tourism. Tourist objects in Solo City were varied from traditional, namely Kasunanan Solo Palace, to modern, such as Beteng Trade Center. Tourists are freely to visit those tourist objects and bought souvenirs that were easily to found around the city. This study aim to describe tourist’s characteristics who visited Solo City. The characteristics were divided into demographic aspect, physiologic aspect, and tourist trip pattern. Method used in this study was mixed and questionnaires were distributed among 100 respondents, then result was describe into preferred aspects. The results were clustered into specific aspects. Demographic aspect showed that most of the tourist was woman, aged between 15-24 years old, the majority of respondents were not civil servant or industrial labor, high school graduated, and not married. Physiologic aspect showed majority of respondents visited Solo City no more than 12 hours, and spend mostly on trip cost. Lastly, from tourist trip pattern, majority were traveled with non-family group, for holiday purposed, and arranged independently. Key words: characteristic, demographic, physiologic, tourism, trip